Effectiveness of Using Pakcoy (Brassica rapa L.) and Kailan (Brassica oleracea) Plants as Vegetable Media for Aquaponic Culture of Tilapia (Oreochromis sp.) - Heri Ariadi; Immanuel A.H. Pandaingan; Agoes Soeprijanto; Yunita Maemunah; Abdul Wafi (Universitas Tidar, 2020)
Aquaponic is one way to use a narrow area of land as a medium for fish cultivation and vegetables in one compartment. The types of commodities that are often cultivated using this system are tilapia fish, pakcoy vegetables, and kailan plants. The purpose of this study was to assess the effectiveness the use of pakcoy (Brassica rapa L.) and kailan (Brassica oleracea) on growth rates and feed conversion ratios by tilapia fish (Oreochromis sp.) cultivated in aquaponic aquaculture systems. The method used was an experimental design with a completely randomized using 3 treatments and 3 replications. The main parameters analyzed in this study were the specific growth rate (SGR) and the fish feed conversion ratio (FCR). Meanwhile, the supporting parameters measured include water quality variables such as temperature, pH, dissolved oxygen, ammonia, nitrite and nitrate. The results showed, during the maintenance of tilapia fish (Oreochromis sp.) with an aquaponic system, pakcoy (Brassica rapa L.) and kailan plants (Brassica oleracea) had an effect on increasing growth rate and feed conversion ratio by tilapia (Oreochromis sp.). In addition, during the maintenance period the water quality parameters also tend to be stabilized and comply with quality standards. The conclusion from this research is that the application of kalian plant (Brassica oleracea) use in the aquaponic system of tilapia commodities is more effective than pakcoy plants (Brassica rapa L.) with an effective SGR value at 3.15% and an FCR value at 1.21.